Redetermination of the low-temperature polymorph of Li(2)MnSiO(4) from single-crystal X-ray data - Sato, Mineo (International Union of Crystallography, 2012)
Crystals of dilithium manganese(II) silicate were grown under high-temperature hydrothermal conditions in the system LiOH—MnO(2)—SiO(2). The title compound crystallizes in the β(II)-Li(3)PO(4) structure type. The coordination polyhedra of all cations are slightly distorted tetrahedra (m symmetry for MnO(4) and SiO(4)), which are linked by corner-sharing to each other. The vertices of the tetrahedra point to the same direction perpendicular to the distorted hexagonal close-packed (hcp) array of O atoms within which half of the tetrahedral voids are occupied by cations. In comparison with the previous refinement from powder X-ray data [Dominko et al. (2006 ▶). Electrochem. Commun. 8, 217–222], the present reinvestigation from single-crystal X-ray data allows a more precise determination of the distribution of the Li(+) and Mn(2+) cations, giving a perfectly site-ordered structure model for both Li(+) and Mn(2+).